Soil Macrofauna Diversity in Gold Mine Tailing Storage Facilities (TSF) Mirah I and TSF Mirah II at PT Kasongan Bumi Kencana: Keragaman Makrofauna Tanah di Fasilitas Penyimpanan Tailing Tambang Emas (TSF) Mirah I dan TSF Mirah II di PT Kasongan Bumi Kencana. - Putir, Patricia Erosa; Wahyudi, Wahyudi; Winarti, Sih; Sosilawaty, Sosilawaty (Universitas Muhammadiyah Sidoarjo, 2023)
This research focuses on the assessment of soil macrofauna in gold mine tailing storage facilities (TSF) at PT Kasongan Bumi Kencana. The study aimed to analyze the physical and chemical properties of the soil, identify soil macrofauna, and evaluate their diversity in TSF Mirah I (7 years old) and TSF Mirah II (1 year old). Using a descriptive-quantitative approach, 38 subplots were established within each TSF, and data on macrofauna were collected, analyzed, and presented through descriptive statistics and species diversity index calculations. The results revealed that both TSFs exhibited low organic matter content. Mirah I TSF harbored 15 families with 172 individuals, primarily dominated by the Trigoniulidae (millipedes) family. In contrast, Mirah II TSF contained 14 families with 120 individuals, mainly dominated by the Formicidae (black ant) family. The diversity index for Mirah I TSF was moderate (H’=1.9911), similar to Mirah II TSF (H’=1.8665). These findings highlight the potential of soil macrofauna as bioindicators for assessing tailing quality in gold mine operations. Highlights: Examined physical and chemical properties of soil and identified soil macrofauna in two gold mine tailing storage facilities (TSF) at PT Kasongan Bumi Kencana. Utilized a descriptive-quantitative approach and species diversity index to analyze the macrofauna data. Trigoniulidae (millipedes) dominated in Mirah I TSF, while Formicidae (black ant) dominated in Mirah II TSF, with both TSFs showing a moderate diversity index.